(untitled) (African Journal of Public Administration & Management, 2026)
Mozambique’s youth bulge poses urgent challenges for economic inclusion and state–society trust. This mixed-methods study (quantitative data + qualitative fieldwork across Nampula, Cabo Delgado, Niassa, with comparison to Gaza) examines how youth cooperatives convert demographic potential into economic, social and institutional gains. Findings show cooperatives act as “infrastructures of hope”: they raise members’ incomes, improve market access, strengthen social solidarity and create structured interfaces with local authorities that rebuild administrative legitimacy. Impacts are stronger in fragile northern contexts; persistent constraints include financial sustainability, uneven institutional uptake and vulnerability to shocks. Policy priorities include performance-linked seed finance, procurement pre-qualification and simple monitoring dashboards.